A Review of a Workers' Compensation Database 2003 to 2013: Patient Factors Influencing Return to Work and Cumulative Financial Claims After Rotator Cuff Repair in Geriatric Workers' Compensation Cases. (December 2017) - Shields, Edward; Thirukumaran, Caroline; Noyes, Katia; Voloshin, Ilya
Background: Workers' compensation status is associated with poor outcomes after rotator cuff repair surgery. The purpose of this study was to analyze a database of geriatric workers' compensation patients after surgical repair of the rotator cuff and identify both medical and nonmedical patient factors that influence the time it takes for them to return to work at full duty, including a comparison of arthroscopic and open techniques. Methods: An all workers' compensation database was queried for rotator cuff claims that were surgically managed using arthroscopic, open, or both approaches from 2003 to 2013 in patients aged ≥60. Primary outcomes were the number of days for return to full work (RTW) following surgery and the total reimbursement for health care. Multivariate analysis was performed, and data are presented as average ± standard deviation. Results: The database yielded 1903 claims for surgically treated rotator cuff conditions (arthroscopic n = 935; open n = 926; both n = 42). In multivariate RTW analyses, we did not find a significant difference between groups (RTW in days was 153 ± 134 for arthroscopy [ P = .81], 160 ± 160 for open [Ref], and 140 ± 82 days for both [ P = .75]). However, multivariate analysis of reimbursement claims found arthroscopic surgery claims to be 13% higher compared to claims for open surgery only (US 29 986 ± 16 259 for arthroscopy vs US 26 495 ± 13 186 for open, P < .001). Patients aged ≥65 had more medical expenses than patients aged 60 to 64 ( P = .03). Potentially modifiable variables that significantly prolonged RTW timing and higher health-care claims included need for vocational rehabilitation services and filing of a legal suit. Conclusions: Return to full-duty work in geriatric workers' compensation patients after rotator cuff repair takes about 5 months regardless of surgical approach and costs significantly more in patients aged ≥65. Arthroscopic repairs generated 13% more cumulative health-care costs than open surgery alone. More efficient vocational rehabilitation services and minimizing legal suits may help get patients back to work sooner and reduce overall costs.